Species-level identity of Pisolithus influences soil phosphorus availability for host plants and is moderated by nitrogen status, but not CO2. (February 2022) - Stuart, Emiko K.; Castañeda-Gómez, Laura; Macdonald, Catriona A.; Wong-Bajracharya, Johanna; Anderson, Ian C.; Carrillo, Yolima; Plett, Jonathan M.; Plett, Krista L.
Abstract: Trees are dependent on the activity of soil microorganisms, including mutualistic ectomycorrhizal (ECM) fungi and soil-dwelling bacteria, for access to phosphorus (P). While P is a key limiting nutrient in temperate and other forest ecosystems, our understanding of the contributions of ECM fungi to plant P nutrition and cycling are unclear. Further complicating our understanding of these processes are the combined effects of fungal species and future climate scenarios and soil nutrient availability. In this study we characterised how the ECM fungi Pisolithus albus and Pisolithus microcarpus influenced the amount of plant-available P in soils and plant P content of Eucalyptus grandis. We explored how these fungi influence P cycling by studying their relative P-solubilising and P-mineralising abilities and examining their impact on P cycling gene abundance in the soil bacterial community. These were investigated under different levels of nitrogen addition and atmospheric CO2 to understand how these processes may be impacted by future anthropogenic and climactic change. While inoculation with either P. albus or P. microcarpus resulted in an increase in plant-available P in soil, the amount of plant-available P mobilised was species-specific. This observation was supported by differences in the in vitro P-mobilising abilities of the two fungi. P. albus and P. microcarpus also favoured bacterial communities characterised by a greater abundance of glucose dehydrogenase gene copies for inorganic P solubilisation, complementing the strengths of the ECM fungi in organic P mineralisation and suggesting a distinction in the roles of ECM fungi and bacteria in P cycling. Furthermore, both nitrogen and CO2 levels impacted these P cycling outcomes, often in a species-specific manner. Our findings expand the current understanding of P cycling between forest trees, ECM fungi and soil bacteria, and have important implications for estimations of future anthropogenic impacts on forest ecosystems. Highlights: Pisolithus increases soil available phosphorus for host in species-dependent manner. Soil bacteria complement role of ectomycorrhizal fungi in phosphorus mobilisation. Soil nitrogen and CO2 levels affect phosphorus cycling in ectomycorrhizal symbiosis.